Uncovering the Industrial Potentials of Lemongrass Essential Oil as a Food Preservative: A Review - Fatima Faheem; Zhi Wei Liu; Roshina Rabail; Iahtisham-Ul Haq; Maryam Gul; Marcin Bryła; Marek Roszko; Marek Kieliszek; Ahmad Din; Rana Muhammad Aadil (MDPI AG, 2022)
The food industry is growing vastly, with an increasing number of food products and the demand of consumers to have safe and pathogen-free food with an extended shelf life for consumption. It is critical to have food safe from pathogenic bacteria, fungi, and unpleasant odors or tastes so that the food may not cause any health risks to consumers. Currently, the direction of food industry has been shifting from synthetically produced preservatives to natural preservatives to lower the unnecessary chemical burden on health. Many new technologies are working on natural prevention tools against food degradation. Lemongrass is one such natural preservative that possesses significant antimicrobial and antioxidant activity. The essential oil of lemongrass contains a series of terpenes that are responsible for these activities. These properties make lemongrass acceptable in the food industry and may fulfill consumer demands. This article provides detailed information about the role of lemongrass and its essential oil in food preservation. The outcomes of the research on lemongrass offer room for its new technological applications in food preservation.